2002
DOI: 10.1002/ca.10059
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch variation analyzed by using plastination

Abstract: Different ramification patterns can be observed during the development of the aortic arch. In this study a common trunk (CT), which subsequently branched into the brachiocephalic trunk (BT) and left common carotid artery (LCCA), arose from the aortic arch. The LCCA arose from the CT 10.27 mm above the aortic arch. After crossing the ventral aspect of the trachea and esophagus, the LCCA became situated on the left side of the esophagus. The caliber and length of the main branches of the aortic arch were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…This points out different propensities for and/or resistance to shrinkage during cold acetone dehydration, impregnation, and curing by different tissues. When measurements are taken before and after plastination to calculate shrinkage to be able to correct the final results (Sora et al, 2002;Sebe et al, 2005;Sora and Genser-Strobl, 2005), all tissue types present in the specimens should be considered. This is especially important when morphometry is made in specimens with two or more tissues with likely very different rates of shrinkage, that is, bone versus soft tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This points out different propensities for and/or resistance to shrinkage during cold acetone dehydration, impregnation, and curing by different tissues. When measurements are taken before and after plastination to calculate shrinkage to be able to correct the final results (Sora et al, 2002;Sebe et al, 2005;Sora and Genser-Strobl, 2005), all tissue types present in the specimens should be considered. This is especially important when morphometry is made in specimens with two or more tissues with likely very different rates of shrinkage, that is, bone versus soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al (2002) and Reed and Henry (2002) used fluid displacement to quantify shrinkage of a variety of organs, which were dehydrated with either room temperature or cold acetone. Sora et al (2002) used scanned images of slices and morphometrics to identify two-dimensional (area) shrinkage associated with cold (À25 C) acetone dehydration, which was 2.13%. As well, shrinkage associated with room temperature degreasing using acetone plus impregnation with epoxy resin plus curing was measured as 4.52%.…”
Section: Introductionmentioning
confidence: 99%
“…The main steps for this method are preparing thin slices of the desired specimen, cold dehydration, degreasing, impregnation, and finally curing (von Hagens, 1986;Lane, 1990;Weber and Henry, 1993;Cook, 1996;Cook and Al-Ali, 1997;Fasel et al, 1988;An and Zhang, 1999;Sora et al, 2002;Sora et al, 2004). Ultrathin slice plastination produces slices with a thickness of 1 mm down to 0.3 mm (Johnson et al, 2000;Windisch and Weiglein, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In a Kenyan population in Africa, the incidence of this variation was found to be 25.7% of the 113 aortic arches of adult cadavers [6]. Sora et al [10] reported a similar case in which the brachiocephalic and left common carotid arteries arose from a common trunk. Rea et al [5] found this variation in 22% (302/1359) patients who had undergone Multi-Detector Computed Tomography Angiography.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians must be aware of possible variations in these major arteries when performing procedures such as needle biopsies or injections [11]. Although anomalous origins of the aortic arch branches are merely anatomic variants, accurate information about them is vital for safe endovascular surgeries aortic instrumentation and angiographies in the thorax, head and neck region [6,10,12,13,18,19]. Variations in branching pattern of the aortic arch may cause dyspnoea, dysphagia, intermittent claudication, misinterpretation of radiological examinations and complications during neck and thorax surgery and may be accompanied by other congenital abnormalities [14,18,19].…”
Section: Introductionmentioning
confidence: 99%